Method for producing fluorine-containing polymer, aqueous dispersion and solid composition
The method addresses the environmental concerns of emulsifier use in fluoropolymer production by polymerizing tetrafluoroethylene in an aqueous dispersion with a low glass transition temperature fluorine-containing polymer, achieving efficient and emulsifier-free fluoropolymer production.
Patent Information
- Application Number
- JP2024570600
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-04-10
- Filing Date
- 2024-04-05
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-04-05
AI Technical Summary
Existing methods for producing fluoropolymers in an aqueous medium often require emulsifiers, which can lead to environmental concerns and the need for emulsifier removal in the final product.
A method for producing fluoropolymers that involves polymerizing a monomer containing tetrafluoroethylene in an aqueous dispersion with a first fluorine-containing polymer having a glass transition temperature of 10° C. or less, without the need for an emulsifier, by controlling the concentration of the first fluoropolymer and the fluorine-based emulsifier.
This method efficiently produces fluoropolymers with high molecular weight without the use of emulsifiers, reducing environmental impact and simplifying the production process.
Smart Images

Figure 0007658519000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a fluorine-containing polymer, an aqueous dispersion and a solid composition. [Background technology]
[0002] Fluorine-containing polymers such as tetrafluoroethylene copolymers are used in various industrial fields because of their excellent heat resistance, chemical resistance, flame retardancy, weather resistance, and the like. As a method for producing a fluorine-containing polymer, there is mentioned a method in which a fluorine-containing emulsifier is used to emulsion-polymerize a fluorine-containing monomer in an aqueous medium (see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2007 / 046377 Summary of the Invention [Problem to be solved by the invention]
[0004] The production method for a fluoropolymer described in Patent Document 1 has a small environmental impact since an aqueous medium is used. However, when a large amount of an emulsifier, which is an essential component, remains in the aqueous dispersion obtained by polymerization, it becomes necessary to remove the emulsifier depending on the application.
[0005] An object of the present invention is to provide a method for producing a fluoropolymer, which can efficiently produce a fluoropolymer using an aqueous medium which has a small environmental load and does not require an emulsifier as an essential component. Another object of the present invention is to provide an aqueous dispersion and a solid composition. [Means for solving the problem]
[0006] As a result of intensive research, the present inventors have found that the above problems can be solved by the following configuration. [1] A method for producing a fluoropolymer, comprising polymerizing a monomer containing tetrafluoroethylene in an aqueous dispersion containing a first fluoropolymer having a glass transition temperature of 10°C or less, and an aqueous medium, to produce a second fluoropolymer different from the first fluoropolymer, wherein the content of the first fluoropolymer is 0.01 to 4.0% by mass based on the total mass of the aqueous dispersion before the start of polymerization of the monomer, The method for producing a fluorine-containing polymer, wherein the concentration of the fluorine-containing emulsifier is 100 ppm by mass or less based on the total mass of the first fluorine-containing polymer in the aqueous dispersion before the start of polymerization of the monomers. [2] The process for producing a fluorine-containing polymer according to [1], wherein the first fluorine-containing polymer contains units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether). [3] The method for producing a fluorine-containing polymer according to [2], wherein in the first fluorine-containing polymer, the units based on perfluoro(alkyl vinyl ether) account for 20 to 60 mol % of the units based on perfluoro(alkyl vinyl ether) relative to the total of the units based on tetrafluoroethylene and the units based on perfluoro(alkyl vinyl ether). [4] The method for producing a fluorinated polymer according to any one of [1] to [3], wherein the amount of the monomer used is 1 to 50 parts by mass per 100 parts by mass of the aqueous medium used. [5] The method for producing a fluorine-containing polymer according to any one of [1] to [4], wherein the monomers are polymerized in the presence of a polymerization initiator. [6] An aqueous dispersion comprising an aqueous medium, a first fluoropolymer having a glass transition temperature of 10°C or lower, and a second fluoropolymer which contains units based on tetrafluoroethylene and is different from the first fluoropolymer, wherein a temperature T showing the maximum endothermic amount in the range of 10 to 35°C of a solid composition obtained by aggregating the aqueous dispersion, as measured by the following method, is 19°C or lower. How to measure the temperature T: A solid composition that has not been heated to a temperature of 300° C. or higher is measured using a differential scanning calorimeter at a heating rate of 10° C. / min. [7] A solid composition comprising a first fluoropolymer having a glass transition temperature of 10°C or lower, and a second fluoropolymer which contains units based on tetrafluoroethylene and is different from the first fluoropolymer, wherein the temperature T showing the maximum endothermic amount of the solid composition in the range of 10 to 35°C, as measured by the following method, is 19°C or lower. How to measure the temperature T: A solid composition that has not been heated to a temperature of 300° C. or higher is measured using a differential scanning calorimeter at a heating rate of 10° C. / min. [8] A solid composition obtained by agglomerating the aqueous dispersion according to [6], wherein the temperature T showing the maximum endothermic amount in the range of 10 to 35°C is 19°C or lower. How to measure the temperature T: A solid composition that has not been heated to a temperature of 300° C. or higher is measured using a differential scanning calorimeter at a heating rate of 10° C. / min. [9] The aqueous dispersion according to [6], wherein the content of units based on perfluoro(alkyl vinyl ether) is 0.1 to 5.0 mol % relative to the total of all units in the first fluorinated polymer and the second fluorinated polymer, and the content of the compound represented by formula (S1) and the content of the compound represented by formula (S2) are each 100 ppb by mass or less relative to the total mass of the first fluorinated polymer and the second fluorinated polymer. Formula (S1): H-(CF2) n―1 -COOM Formula (S2): H-(CF2) n -SO3M In formula (S1) and formula (S2), M each independently represents a hydrogen atom, Na, K, or NH 4 , and n each independently represents 8 or 10.
[10] The solid composition according to [7], wherein the content of units based on perfluoro(alkyl vinyl ether) is 0.1 to 5.0 mol % relative to the total of all units in the first fluorinated polymer and the second fluorinated polymer, and the content of the compound represented by formula (S1) and the content of the compound represented by formula (S2) are each 100 ppb by mass or less relative to the total mass of the first fluorinated polymer and the second fluorinated polymer. Formula (S1): H-(CF2) n―1 -COOM Formula (S2): H-(CF2) n -SO3M In formula (S1) and formula (S2), M each independently represents a hydrogen atom, Na, K, or NH 4 , and n each independently represents 8 or 10. Effect of the Invention
[0007] According to the present invention, there can be provided a method for producing a fluoropolymer, which can efficiently produce a fluoropolymer using an aqueous medium which has a small environmental load and does not require an emulsifier as an essential component. The present invention also provides aqueous dispersions and solid compositions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The terms used in the present invention have the following meanings. A numerical range expressed using "~" means a range including the numerical values before and after "~" as the upper and lower limits. In the numerical ranges described in stages in this specification, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in this specification, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples. In the present specification, each component may be used alone or in combination of two or more substances corresponding to each component. When two or more substances are used in combination for each component, the content of the component refers to the total content of the substances used in combination, unless otherwise specified. As used herein, a combination of two or more preferred embodiments is a more preferred embodiment. The term "unit" refers collectively to an atomic group derived from one molecule of a monomer that is formed directly by polymerization of the monomer, and an atomic group obtained by chemically converting a part of the atomic group. Hereinafter, a "unit based on a monomer" will also be simply referred to as a "unit". The content (mass % or mol %) of each unit relative to the total units contained in the polymer is determined by analyzing the polymer by solid-state nuclear magnetic resonance spectroscopy (NMR), and usually, the content of each unit calculated from the charged amount of each monomer is approximately equal to the actual content of each unit.
[0009] [Method of producing fluorine-containing polymer] The method for producing a fluoropolymer of the present invention (hereinafter also referred to as "the present production method") is a method for producing a second fluoropolymer different from the first fluoropolymer by polymerizing a monomer containing tetrafluoroethylene (hereinafter also referred to as "specific monomer") in an aqueous dispersion containing a first fluoropolymer having a glass transition temperature of 10°C or lower, and an aqueous medium. In the present production method, before the start of polymerization of the monomers, the content of the first fluorine-containing polymer is 0.01 to 4.0% by mass based on the total mass of the aqueous dispersion. In the present production method, before the start of polymerization of the monomers, the concentration of the fluorine-containing emulsifier is 100 ppm by mass or less based on the total mass of the first fluorine-containing polymer in the aqueous dispersion.
[0010] The reason why the second fluoropolymer was efficiently produced by this production method without the essential use of an emulsifier is presumably because the use of an aqueous dispersion containing a predetermined amount of the first fluoropolymer having a glass transition temperature of 10°C or lower allowed the first fluoropolymer to function as a good polymerization site for the second fluoropolymer.
[0011] <Aqueous dispersion> In the present production method, an aqueous dispersion containing a first fluorine-containing polymer and an aqueous medium is used.
[0012] (First fluoropolymer) It is presumed that the first fluoropolymer solubilizes the specific monomer by adsorbing and incorporating the specific monomer at the hydrophobic portion during polymerization of the specific monomer, and that the specific monomer is polymerized within the particles of the first fluoropolymer by adding a polymerization initiator thereto. It is also presumed that the first fluoropolymer contributes to dispersion stabilization in the aqueous medium.
[0013] The first fluoropolymer has a glass transition temperature (hereinafter also referred to as "Tg") of 10°C or lower. The Tg of the first fluoropolymer is preferably 5° C. or lower, more preferably 3° C. or lower, and even more preferably 0° C. or lower, from the viewpoint of efficiently adsorbing the specific monomer. The Tg of the first fluoropolymer is preferably -50°C or higher, more preferably -45°C or higher, and even more preferably -40°C or higher, from the viewpoint of thermal stability after molding. The Tg of the first fluoropolymer is measured by differential scanning calorimetry (DSC), and the detailed measurement conditions are as described later in the Examples section. As a method for adjusting the Tg of the first fluoropolymer within the above range, for example, a method of adjusting the type and amount of monomer used in the production of the first fluoropolymer may be mentioned.
[0014] The first fluorine-containing polymer preferably contains units based on tetrafluoroethylene (hereinafter also referred to as "TFE") (hereinafter also referred to as "TFE units") and units based on perfluoro(alkyl vinyl ether) (hereinafter also referred to as "PAVE units"), from the viewpoints of ease of adjusting Tg to within the above range and of better effects of the present invention.
[0015] As the PAVE, a monomer represented by formula (1) is preferred from the viewpoints of excellent polymerization reactivity in producing the first fluoropolymer and of enabling the second fluoropolymer to be produced more efficiently. CF2=CF-OR f1 (1) In formula (1), R f1 R represents a perfluoroalkyl group having 1 to 10 carbon atoms. f1The number of carbon atoms in the alkyl group is preferably 1 to 8, more preferably 1 to 6, further preferably 1 to 5, and particularly preferably 1 to 3, from the viewpoint of superior polymerization reactivity. The perfluoroalkyl group may be linear or branched.
[0016] Specific examples of PAVE include perfluoro(methyl vinyl ether) (hereinafter also referred to as "PMVE"), perfluoro(ethyl vinyl ether) (hereinafter also referred to as "PEVE"), and perfluoro(propyl vinyl ether) (hereinafter also referred to as "PPVE"). Among these, PMVE and PPVE are preferred, with PMVE being more preferred, from the viewpoint of enabling the second fluorine-containing polymer to be produced more efficiently.
[0017] When the first fluorine-containing polymer contains TFE units and PAVE units, the content of the PAVE units in the first fluorine-containing polymer relative to the total of the TFE units and PAVE units is preferably 20 to 60 mol%, more preferably 25 to 60 mol%, and even more preferably 30 to 55 mol%, from the viewpoints that Tg can be easily adjusted to the above range and that the second fluorine-containing polymer can be produced more efficiently.
[0018] The first fluorine-containing polymer may contain units based on monomers other than TFE and PAVE, but from the viewpoint of more efficient production of the second fluorine-containing polymer, it is preferable that the first fluorine-containing polymer is substantially free of units based on other monomers. Substantially free of units derived from other monomers means that the content of units derived from other monomers is 0.01 mol % or less, more preferably 0 mol %, based on the total units of the first fluorine-containing polymer. When units based on another monomer are contained, the other monomer is preferably hexafluoropropylene.
[0019] Before starting polymerization of the monomers to be used in polymerization of the second fluoropolymer, the content of the first fluoropolymer is 0.01 to 4.0 mass% based on the total mass of the aqueous medium in the aqueous dispersion, and from the viewpoint of producing the second fluoropolymer more efficiently, it is preferably 0.01 to 0.6 mass%, more preferably 0.01 to 0.5 mass%.
[0020] In this specification, "before initiating polymerization of the monomers used in the polymerization of the second fluoropolymer" means immediately before the start of polymerization. Here, examples of "the start of polymerization" include the time when the monomers and the polymerization initiator are made to coexist in the reactor after the temperature inside the reactor is raised to the polymerization temperature or higher, and the time when the temperature inside the reactor is raised to the polymerization temperature or higher after the monomers and the polymerization initiator are made to coexist in the reactor.
[0021] Before starting polymerization of the monomers used in the polymerization of the second fluorine-containing polymer, the concentration of sulfate ions is preferably 10 ppm by mass or less, more preferably 5 ppm by mass or less, based on the total mass of the aqueous medium in the aqueous dispersion, from the viewpoint of suppressing coloration of the second fluorine-containing polymer.The lower limit is 0 ppm by mass. One example of a method for adjusting the sulfate ion concentration to the above range is to remove sulfate ions using an anion exchange resin during the production of the first fluoropolymer. Here, the sulfate ion originates, for example, from a polymerization initiator (particularly, ammonium persulfate) used in producing the first fluoropolymer, and may be contained in the aqueous dispersion containing the first fluoropolymer. It is presumed that by making the content of sulfate ions 10 ppm by mass or less (particularly, 5 ppm by mass or less), it is possible to suppress the formation of terminal groups with low heat resistance in the second fluoropolymer, thereby suppressing coloration of the second fluoropolymer.
[0022] Before starting polymerization of the monomers used in the polymerization of the second fluoropolymer, the concentration of ammonium ions is preferably 20 ppm by mass or less, more preferably 10 ppm by mass or less, based on the total mass of the aqueous medium in the aqueous dispersion, from the viewpoint of suppressing aggregation of the second fluoropolymer.The lower limit is 0 ppm by mass. One example of the method for adjusting the ammonium ion concentration to the above range is to remove the ammonium ions using a cation exchange resin during the production of the first fluorinated polymer. Here, the ammonium ion is derived, for example, from an initiator (particularly ammonium persulfate) used in the production of the first fluoropolymer, and may be contained in the aqueous dispersion containing the first fluoropolymer. It is presumed that the ammonium ion content of 20 ppm by mass or less reduces the ionic strength in the aqueous medium, thereby improving the production efficiency of the second fluoropolymer.
[0023] The first fluoropolymer is preferably dispersed in the aqueous medium in the form of particles. In this case, the average particle size of the first fluoropolymer is preferably from 1 to 150 nm, more preferably from 10 to 120 nm, and even more preferably from 50 to 120 nm, from the viewpoint of enabling the second fluoropolymer to be produced more efficiently. The average particle diameter of the first fluoropolymer is the particle diameter (D50) at the point on the cumulative curve where the cumulative volume is 50% when the particle size distribution is measured by a laser diffraction / scattering method and the total volume of the particle group is set to 100%, and the detailed measurement conditions are as described in the Examples section.
[0024] The method for producing the first fluorine-containing polymer is preferably a method for polymerizing a monomer (preferably a monomer mixture containing TFE and PAVE) in an aqueous medium in the presence of a polymerization initiator, thereby obtaining the first fluorine-containing polymer dispersed in the aqueous medium in the form of particles. The aqueous medium thus obtained in which the particles of the first fluoropolymer are dispersed may be used as it is as the aqueous dispersion, or another aqueous medium may be added thereto and used as the aqueous dispersion. Alternatively, the first fluoropolymer may be dispersed in another aqueous medium by solvent replacement and used as the aqueous dispersion.
[0025] The polymerization initiator used in the production of the first fluorine-containing polymer is preferably a water-soluble polymerization initiator, more preferably a persulfate such as ammonium persulfate, sodium persulfate or potassium persulfate, or an organic polymerization initiator such as disuccinic acid peroxide or azobisisobutylamidine dihydrochloride, further preferably a persulfate, and particularly preferably ammonium persulfate.
[0026] The aqueous medium used in the production of the first fluorine-containing polymer may be water or a mixed solvent of water and a water-soluble organic solvent. Specific examples of the water-soluble organic solvent include tert-butanol, propylene glycol, dipropylene glycol, dipropylene glycol monomethyl ether, and tripropylene glycol.
[0027] The method for producing the first fluoropolymer preferably includes a heating step of heating the aqueous medium in which the first fluoropolymer is dispersed after obtaining the aqueous medium. This deactivates the polymerization initiator present in the system, so that the polymerization of the second fluoropolymer is less affected by the polymerization initiator used in producing the first fluoropolymer. As a result, the second fluoropolymer having a high molecular weight is easily obtained. The heating temperature in the heating step is preferably from 70 to 100° C., more preferably from 80 to 98° C., and even more preferably from 85 to 95° C., since this can further promote the deactivation of the polymerization initiator in the aqueous medium.
[0028] (aqueous medium) The aqueous dispersion used in the present production method contains an aqueous medium. The aqueous medium contained in the aqueous dispersion may be the polymerization solvent used in the production of the first fluoropolymer, as described above. Specific examples of the aqueous medium contained in the aqueous dispersion are the same as the specific examples of the aqueous medium used in producing the above-mentioned first fluorine-containing polymer. Before starting polymerization of the monomers used in the polymerization of the second fluorine-containing polymer, the content of the aqueous medium is preferably from 60 to 99.9 mass%, more preferably from 96 to 99.9 mass%, and even more preferably from 98 to 99.9 mass%, based on the total mass of the aqueous dispersion.
[0029] (Other ingredients) The aqueous dispersion used in the present production method may contain other components in addition to the first fluorine-containing polymer and the aqueous medium. Specific examples of other components that may be contained in the aqueous dispersion include a chain transfer agent, an emulsifier other than a fluorine-based emulsifier, a pH adjuster, and a wax.
[0030] Specific examples of chain transfer agents include ethyl acetate, methanol, ethanol, t-butyl methyl ether, diethyl ether, n-pentane, cyclohexane, methane, and propane.
[0031] Specific examples of emulsifiers other than fluorine-based emulsifiers include sodium lauryl sulfate, Pelex SS-H manufactured by Kao Chemical Co., Ltd., and Newcol 1305-SN manufactured by Nippon Nyukazai Co., Ltd.
[0032] Specific examples of pH adjusters include inorganic salts. Specific examples of inorganic salts include phosphates such as disodium hydrogen phosphate and sodium dihydrogen phosphate, and carbonates such as sodium hydrogen carbonate and sodium carbonate. More preferred specific examples of phosphates include disodium hydrogen phosphate dihydrate and disodium hydrogen phosphate dodecahydrate.
[0033] Specific examples of wax include Parafffin Wax-155 and Parafffin Wax-150 (both manufactured by Nippon Seiro Co., Ltd.).
[0034] When the aqueous dispersion contains a chain transfer agent, the content of the chain transfer agent is preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the aqueous medium, and the amount of the chain transfer agent used is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, and even more preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of the specific monomer used, which will be described later. When the aqueous dispersion contains an emulsifier other than a fluorine-based emulsifier, the content of the emulsifier other than a fluorine-based emulsifier is preferably 0.01 to 5 parts by mass with respect to 100 parts by mass of the aqueous medium. When the aqueous dispersion contains a pH adjuster, the content of the pH adjuster is preferably 0.01 to 3.0 parts by mass relative to 100 parts by mass of the aqueous medium. When the aqueous dispersion contains a wax, the content of the wax is preferably 1 to 10 parts by mass with respect to 100 parts by mass of the aqueous medium.
[0035] Before starting polymerization of the monomers used in the polymerization of the second fluorine-containing polymer, the concentration of the fluorine-containing emulsifier is 100 ppm by mass or less based on the total mass of the first fluorine-containing polymer in the aqueous dispersion, and from the viewpoint of better effects of the present invention, it is preferably 50 ppm by mass or less, more preferably 25 ppm by mass or less, and even more preferably 5 ppm by mass or less.The lower limit is 0 ppm by mass. The fluorine-containing emulsifier means an emulsifier in which the hydrophobic moiety contains a fluorine atom among the hydrophilic moiety and the hydrophobic moiety of the emulsifier. Specific examples of the fluorine-containing emulsifier include fluorine-containing alkanoates and fluorine-containing ether carboxylic acid compounds. One example of a method for adjusting the concentration of the fluorine-based emulsifier to fall within the above range is a method for producing an aqueous dispersion without using a fluorine-based emulsifier.
[0036] Before starting polymerization of the monomers used in the polymerization of the second fluorine-containing polymer, the concentration of fluoride ions is preferably 100 ppm by mass or less, more preferably 50 ppm by mass or less, based on the total mass of the aqueous dispersion, from the viewpoint of polymerization stability. The lower limit is 0 ppm by mass. One example of a method for adjusting the fluoride ion concentration to the above range is to remove sulfate ions using an anion exchange resin during the production of the first fluorinated polymer. Here, the fluoride ions may be generated by the reaction between a polymerization initiator (eg, ammonium persulfate) and a monomer used in the production of the first fluorine-containing polymer, and may be contained in the aqueous dispersion.
[0037] <Specific monomer> Specific monomers include TFE. The amount of TFE used is preferably from 97 to 100% by mass, more preferably from 98 to 100% by mass, and even more preferably from 99 to 100% by mass, based on the amount of the specific monomer used.
[0038] The specific monomer may contain a fluorine-containing monomer other than TFE, but may be essentially free of a fluorine-containing monomer other than TFE. "Substantially free of fluorine-containing monomers other than TFE" means that the amount of fluorine-containing monomers other than TFE used is 0.0001% by mass or less, and may be 0% by mass, based on the amount of the specific monomer used. Examples of the fluorine-containing monomer other than TFE include chlorotrifluoroethylene (hereinafter also referred to as "CTFE"), vinylidene fluoride (hereinafter also referred to as "VdF"), fluoroalkylethylene, PAVE, and hexafluoropropylene. Two or more kinds of the fluorine-containing monomer other than TFE may be used in combination.
[0039] The specific monomer may contain monomers other than the fluorine-containing monomer (hereinafter also referred to as "other monomers"), but it is preferable that the specific monomer does not contain any other monomers. "Substantially free of other monomers" means that the amount of other monomers used is 0.0001% by mass or less, more preferably 0% by mass, based on the amount of the specific monomer used. Specific examples of the other monomer include ethylene, propylene, vinyl chloride, and vinylidene chloride. Two or more of the other monomers may be used in combination.
[0040] The amount of the specific monomer used is preferably 1 to 50 parts by mass, more preferably 1 to 40 parts by mass, and even more preferably 1 to 30 parts by mass, relative to 100 parts by mass of the aqueous medium contained in the aqueous dispersion.
[0041] <Polymerization initiator> In the present production method, the specific monomer is preferably polymerized in the presence of a polymerization initiator. As the polymerization initiator, an oil-soluble radical initiator, a water-soluble radical initiator, or a water-soluble oxidation-reduction catalyst is preferable. Specific examples of oil-soluble radical initiators include oil-soluble organic peroxides such as tert-butyl peroxypivalate (hereinafter also referred to as "PBPV") and diisopropyl peroxydicarbonate (hereinafter also referred to as "IPP"). Specific examples of water-soluble radical initiators include persulfates such as ammonium persulfate and potassium persulfate, water-soluble organic peroxides such as disuccinic acid peroxide, bisglutaric acid peroxide, and tert-butyl hydroperoxide (hereinafter also referred to as "TBHP"). As the water-soluble redox catalyst, a combination of an oxidizing agent such as bromic acid or a salt thereof, chloric acid or a salt thereof, persulfuric acid or a salt thereof, permanganic acid or a salt thereof, or hydrogen peroxide, and a reducing agent such as sulfurous acid or a salt thereof, hydrogen sulfite or a salt thereof, thiosulfuric acid or a salt thereof, an organic acid, or an inorganic salt, is preferred. As the persulfate, potassium persulfate or ammonium persulfate is preferred. As the sulfite, sodium sulfite is preferred. As the inorganic salt, a combination of sulfate anion, sulfite anion, and chloride anion with a metal ion is preferred. As the metal ion, a transition metal is preferred, and examples thereof include ions of manganese, iron, cobalt, nickel, copper, zinc, cerium, and silver, and among these, iron ion is preferred. As the inorganic salt, iron (II) sulfate is preferred. As the polymerization initiator, an oil-soluble radical initiator or a water-soluble radical initiator is preferred, and from the viewpoint of more efficient production of a fluorine-containing polymer, an oil-soluble radical initiator is more preferred, and an oil-soluble organic peroxide is even more preferred. Two or more types of polymerization initiators may be used in combination.
[0042] The amount of the polymerization initiator used is preferably 1 to 1000 ppm, more preferably 5 to 750 ppm, and further preferably 10 to 500 ppm, based on 100 parts by mass of the specific monomer used.
[0043] <Other ingredients> When polymerizing the specific monomer, components other than those described above (hereinafter, also referred to as "other components") may be further used. A specific example of the other components is a reducing agent. The amount of the other components used is preferably 1 to 2000 ppm relative to 100 parts by mass of the specific monomer used.
[0044] <Process> In the present production method, the above specific monomer is polymerized in the above aqueous dispersion to produce the second fluorine-containing polymer.
[0045] The second fluorine-containing polymer obtained by the present production method contains units based on TFE (hereinafter also referred to as "TFE units") and is preferably a homopolymer of TFE (hereinafter also referred to as "PTFE"). The first fluorine-containing polymer and the second fluorine-containing polymer may be copolymerized.
[0046] The content of TFE units in the second fluorinated polymer is preferably from 99.0 to 100.0 mol %, more preferably from 99.5 to 100.0 mol %, and even more preferably from 99.9 to 100.0 mol %, based on all units constituting the second fluorinated polymer.
[0047] The specific monomer is added to the reaction system (i.e., polymerization reaction vessel) by a conventional method. For example, the specific monomer may be added to the reaction system continuously or intermittently so that the polymerization pressure becomes a predetermined pressure. Alternatively, the specific monomer may be dissolved in an aqueous medium, and the obtained solution may be added to the reaction system continuously or intermittently. When a polymerization initiator is used, the polymerization initiator may be added to the reaction system all at once or in portions.
[0048] The polymerization temperature is preferably from 10 to 95°C, more preferably from 15 to 90°C. The polymerization pressure is preferably from 0.5 to 4.0 MPaG, more preferably from 0.6 to 3.5 MPaG. In the case of batch processing, the polymerization time is preferably from 90 to 1000 minutes, more preferably from 90 to 700 minutes.
[0049] The polymerization of the specific monomer is preferably carried out in the substantial absence of an emulsifier. The emulsifier may be any known emulsifier, including a common surfactant. "In the substantial absence of an emulsifier" means an environment in which the content of the emulsifier is 0.03 ppm by mass or less relative to the total mass of the aqueous medium contained in the aqueous dispersion, preferably 0.02 ppm by mass or less, and more preferably 0 ppm by mass.
[0050] As described above, it is presumed that the specific monomer is polymerized within the particles of the first fluorine-containing polymer during polymerization of the specific monomer, and therefore, in the present production method, particles containing the first fluorine-containing polymer and the second fluorine-containing polymer are generated. That is, it is presumed that, in the present production method, the second fluorine-containing polymer is obtained in the form of particles containing the first fluorine-containing polymer and the second fluorine-containing polymer. In this case, the present production method provides an aqueous dispersion in which particles containing the first fluorine-containing polymer and the second fluorine-containing polymer are dispersed in the aqueous medium.
[0051] [Aqueous dispersion] The aqueous dispersion of the present invention (hereinafter also referred to as "the present aqueous dispersion") is an aqueous dispersion containing an aqueous medium, a first fluoropolymer having a Tg of 10°C or lower, and a second fluoropolymer which contains TFE units and is different from the first fluoropolymer. In the present aqueous dispersion, the content of PAVE units relative to the total of all units of the first fluoropolymer and the second fluoropolymer is 0.1 to 5.0 mol %. In addition, in the present aqueous dispersion, the content of the compound represented by formula (S1) described below and the content of the compound represented by formula (S2) described below are each 100 ppb by mass or less, relative to the total mass of the first fluorinated polymer and the second fluorinated polymer.
[0052] The present aqueous dispersion can be obtained, for example, by the present production method described above.
[0053] <First Fluorine-Containing Polymer and Second Fluorine-Containing Polymer> The first fluorine-containing polymer is the same as the first fluorine-containing polymer in the above-mentioned present production method, and preferred embodiments are also the same. A preferred embodiment of the first fluoropolymer contained in the present aqueous dispersion is an embodiment containing TFE units and PAVE units. When the first fluorine-containing polymer contains TFE units and PAVE units, the content of PAVE units in the first fluorine-containing polymer is preferably 20 to 60 mol %, more preferably 25 to 60 mol %, and even more preferably 30 to 55 mol %, based on the total of TFE units and PAVE units.
[0054] The content of the first fluoropolymer is preferably from 0.10 to 1.0 mass %, more preferably from 0.15 to 0.80 mass %, and even more preferably from 0.20 to 0.60 mass %, based on the total mass of the aqueous dispersion.
[0055] The second fluorine-containing polymer is the same as the second fluorine-containing polymer in the above-mentioned present production method, and preferred embodiments are also the same. The second fluorine-containing polymer contained in the aqueous dispersion contains TFE units. The content of TFE units in the second fluorinated polymer is preferably from 99.0 to 100.0 mol %, more preferably from 99.5 to 100.0 mol %, and even more preferably from 99.9 to 100.0 mol %, based on all units constituting the second fluorinated polymer.
[0056] The content of the second fluorine-containing polymer is preferably from 10 to 40 mass %, more preferably from 12 to 35 mass %, and even more preferably from 15 to 30 mass %, based on the total mass of the aqueous dispersion.
[0057] In the present aqueous dispersion, the content of PAVE units based on the total of all units of the first fluoropolymer and the second fluoropolymer is 0.1 to 5.0 mol %, preferably 0.2 to 3.0 mol %, more preferably 0.3 to 2.0 mol %. The PAVE unit may be contained in at least one of the first fluorine-containing polymer and the second fluorine-containing polymer, but is preferably contained in the first fluorine-containing polymer.
[0058] In the present aqueous dispersion, the content of TFE units based on the total of all units of the first fluoropolymer and the second fluoropolymer is preferably from 90 to 99.8 mol %, more preferably from 93 to 99.5 mol %, and even more preferably from 95 to 99.0 mol %. The TFE unit may be contained in at least the second fluorine-containing polymer, but is preferably contained in both the first and second fluorine-containing polymers.
[0059] In the present aqueous dispersion, the total content of the first fluoropolymer and the second fluoropolymer is preferably from 10 to 40 mass%, more preferably from 12 to 35 mass%, and even more preferably from 15 to 35 mass%, based on the total mass of the present aqueous dispersion.
[0060] The first fluoropolymer and the second fluoropolymer may be present separately in the present aqueous dispersion, but it is preferable that they are present in the form of particles containing the first fluoropolymer and the above-mentioned second fluoropolymer. In this case, the average particle size of the particles is preferably 500 μm or less, more preferably 450 μm or less, and even more preferably 400 μm or less, from the viewpoint of dispersion stability. From the viewpoint of aggregation, the average particle size of the particles is preferably 50 nm or more, more preferably 80 nm or more, and even more preferably 100 nm or more. The average particle size of particles is determined by measuring the particle size distribution by a laser diffraction / scattering method, calculating a cumulative curve with the total volume of the particle group as 100%, and determining the particle size at the point on the cumulative curve where the cumulative volume is 50%.
[0061] <Aqueous medium> Specific examples of the aqueous medium contained in the present aqueous dispersion are the same as the specific examples of the aqueous medium used in the production of the above-mentioned first fluoropolymer. The content of the aqueous medium is preferably from 50 to 99 mass%, more preferably from 60 to 99 mass%, and even more preferably from 70 to 99 mass%, based on the total mass of the aqueous dispersion, from the viewpoint of dispersion stability of the first fluoropolymer and the second fluoropolymer.
[0062] <Compound represented by formula (S1) and compound represented by formula (S2)> The compound represented by formula (S1) and the compound represented by formula (S2) are components that can be generated when TFE is polymerized in the presence of a polymerization initiator, a chain transfer agent and an emulsifier (particularly, a hydrocarbon-based emulsifier). Therefore, when no emulsifier is used in the production of the second fluorine-containing polymer contained in the present aqueous dispersion, the generation amount of the compound represented by formula (S1) and the compound represented by formula (S2) can be suppressed, and it becomes easy to set the content of these compounds within the range described below.
[0063] Formula (S1): H-(CF2) n―1 -COOM Formula (S2): H-(CF2) n -SO3M In formula (S1) and formula (S2), M each independently represents a hydrogen atom, Na, K, or NH 4 , and n each independently represents 8 or 10.
[0064] In the present aqueous dispersion, the content of the compound represented by formula (S1) and the content of the compound represented by formula (S2) are each 100 ppb by mass or less, preferably 50 ppb by mass or less, more preferably 25 ppb by mass or less, and even more preferably 0 ppb by mass (i.e., no compound represented by formula (S1) or no compound represented by formula (S2)) relative to the total mass of the first fluorinated polymer and the second fluorinated polymer.
[0065] <Other> The aqueous dispersion of the present invention is preferably substantially free of an emulsifier. Examples of the emulsifier include the above-mentioned fluorine-based emulsifiers and emulsifiers other than fluorine-based emulsifiers. The aqueous dispersion being substantially free of emulsifier means that the content of emulsifier is 0.03 ppm by mass or less, preferably 0.02 ppm by mass or less, and more preferably 0 ppm by mass, relative to the total mass of the aqueous dispersion.
[0066] <Application> As described above, since the present aqueous dispersion does not require an emulsifier, it is easy to make it into a dispersion in an organic solvent such as N-methylpyrrolidone or acetone by solvent substitution. For example, the aqueous dispersion of the present invention can be mixed with an organic solvent and dehydrated using evaporation or anhydrous sodium sulfate or the like to give a dispersion in the organic solvent.
[0067] In this aqueous dispersion, the fluoropolymer is stably dispersed even without the inclusion of an emulsifier, and therefore it is suitable for use in coating applications, as a binder, etc.
[0068] Furthermore, by agglomerating the first fluoropolymer and the second fluoropolymer (preferably particles containing the first fluoropolymer and the second fluoropolymer) from the aqueous dispersion, powders of the first fluoropolymer and the second fluoropolymer can be obtained.
[0069] Flocculation methods include, but are not limited to, freeze flocculation, acid flocculation, base flocculation, and flocculation using a coagulant. In the case of freeze aggregation, the aggregation temperature is preferably −20 to 0° C. The aggregation time is preferably 1 hour or more, more preferably 2 hours or more. In the case of acid coagulation, a method of adding an acid-containing solution to the aqueous dispersion is preferred. Examples of the acid to be added include hydrochloric acid, nitric acid, sulfuric acid, oxalic acid, hydrofluoric acid, etc., and hydrochloric acid is preferred. The concentration of the acid in the acid-containing solution is preferably 0.1 to 50 mass%, more preferably 1 to 30 mass%, and even more preferably 1 to 10 mass%. The base coagulation is preferably carried out by adding a solution containing a base to the aqueous dispersion. Examples of the base to be added include sodium hydroxide, potassium hydroxide, and ammonium carbonate, and sodium hydroxide is preferred. The concentration of the base in the solution containing the base is preferably 0.1 to 50% by mass, more preferably 1 to 30% by mass, and even more preferably 1 to 10% by mass. For the aggregation using a coagulant, a known coagulant can be used. Known coagulants include aluminum salts, calcium salts, and magnesium salts. Specific examples include aluminum sulfate, alum represented by the general formula M'Al(SO4)2·12H2O (wherein M' is a monovalent cation other than lithium), calcium nitrate, and magnesium sulfate. Alum is preferred, and potassium alum, where M is potassium, is more preferred. As the aggregation method, base aggregation is preferred since aggregation is particularly likely to proceed.
[0070] [Solid composition] The solid composition of the present invention (hereinafter also referred to as "the present solid composition") is a solid composition comprising a first fluoropolymer having a glass transition temperature of 10°C or lower, and a second fluoropolymer which contains TFE units and is different from the first fluoropolymer. In the present solid composition, the content of PAVE units relative to the total of all units of the first fluorine-containing polymer and the second fluorine-containing polymer is 0.1 to 5.0 mol %. In addition, in the present solid composition, the content of the compound represented by the above formula (S1) and the content of the compound represented by the above formula (S2) are each 100 ppb by mass or less, relative to the total mass of the first fluorinated polymer and the second fluorinated polymer.
[0071] In this specification, a solid composition means a composition having a solid content of 99% by mass or more. Here, the solid content mass is calculated by the following method based on the mass before and after heating. 2.0 g of the solid composition is heated at 170° C. for 20 minutes, and then the mass of the residue is weighed and the solid content mass is calculated according to the following formula. Solid content mass (mass%)=100×(mass of residue) / (mass of solid composition)
[0072] The present solid composition is preferably obtained by the aggregation method using the present aqueous dispersion described above. The preferred embodiments of the present solid composition are the same as the preferred embodiments of the first fluorine-containing polymer and the second fluorine-containing polymer contained in the present aqueous dispersion described above, and therefore the description thereof will be omitted. The first fluoropolymer and the second fluoropolymer may be present separately in the solid composition, but are preferably present in the form of particles containing the first fluoropolymer and the above-mentioned second fluoropolymer.
[0073] The content of the first fluorine-containing polymer is preferably from 0.1 to 5 mass %, more preferably from 0.2 to 4 mass %, and even more preferably from 0.3 to 3 mass %, based on the total mass of the solid composition. The content of the second fluorine-containing polymer is preferably from 95 to 99.9 mass %, more preferably from 96 to 99.8 mass %, and even more preferably from 97 to 99.7 mass %, based on the total mass of the present solid composition. The total content of the first fluoropolymer and the second fluoropolymer is preferably from 99.0 to 100 mass%, more preferably from 99.5 to 100 mass%, and even more preferably from 99.8 to 100 mass%, based on the total mass of the solid composition.
[0074] <Temperature T> The solid composition obtained by aggregating the aqueous dispersion of the present invention or the solid composition of the present invention preferably has a temperature T at which the maximum endothermic amount is measured in the range of 10 to 35° C. by the method described below is 19° C. or less, more preferably 18° C. or less, and even more preferably 17.5° C. or less. The lower limit of the temperature T is 10° C. By containing the first fluoropolymer and the second fluoropolymer (preferably particles containing the first fluoropolymer and the second fluoropolymer) in the aqueous dispersion, the temperature T can be adjusted to within the above range. EXAMPLES
[0075] The present invention will be described in detail below with reference to examples. Examples 1, 2, 5, and 6 are working examples, and Examples 3, 4, and 7 are comparative examples. However, the present invention is not limited to these examples. The blending amount of each component in the table below is based on mass.
[0076] [Measurement and evaluation methods] The various measurement and evaluation methods are as follows.
[0077] <Glass transition temperature (Tg)> Tg was measured using a Hitachi High-Tech NEXTA DSC600. Specifically, 5 mg of a sample for measurement was weighed out and placed in an aluminum sample pan, and the sample was heated to 100°C at a heating rate of 10°C / min under a nitrogen atmosphere. It was then cooled to -60°C at a rate of 10°C / min. When the specified temperature was reached, the temperature was raised again to 100°C at 10°C / min. Tg was estimated from the inflection point observed in this second heating operation.
[0078] <Average particle size in liquid> The raw material liquid was degassed for 5 minutes at room temperature (25°C), pressurized with nitrogen to 0.2 MPaG, and then purged to atmospheric pressure to obtain a sample for measurement. The particle size of the obtained sample was measured using a laser diffraction / scattering particle size distribution measuring device (Otsuka Electronics Co., Ltd., ELSZ) with the cumulative number set to 100 and measurement was started. D50 was calculated from the particle sizes measured in the range of 1 to 300 nm, and this was taken as the average particle size of the particles in the raw material liquid. The average particle size of the particles in the aqueous dispersion corresponding to the raw material liquid was measured in the same manner as in the raw material liquid, and was found to be the same as that of the particles in the raw material liquid. Here, the aqueous dispersion corresponding to the raw material liquid means aqueous dispersion B corresponding to raw material liquid B in Example 1 described later. The average particle size (D50) of particles in each aqueous dispersion obtained using an aqueous dispersion corresponding to the raw material liquid was measured using a laser diffraction / scattering particle size distribution analyzer (ELSZ, Otsuka Electronics Co., Ltd.). However, the range of particle sizes to be measured was not limited, unlike the method for measuring the average particle size of particles in the raw material liquid. Here, the aqueous dispersion obtained using an aqueous dispersion corresponding to the raw material liquid in each example means aqueous dispersion 1 obtained using aqueous dispersion B in the case of Example 1 described later.
[0079] <Average particle size after drying> The particles obtained in each example were dried and aggregated, and then photographed using a scanning electron microscope (e.g., JSM-IT700HR InTouchScope, manufactured by JEOL Ltd.). The particle sizes of five different particles measured from the obtained SEM images were calculated and the arithmetic mean was calculated.
[0080] <Proportion of each unit in the polymer> The ratio of each unit in the polymer is 19 The values were determined by F-NMR analysis and infrared absorption spectroscopy.
[0081] <Content of compound represented by formula (S1)> The content of the compound represented by the above formula (S1) relative to the total mass of particles in the aqueous dispersion obtained in each example described below was calculated by a method using an aqueous dispersion among the measurement methods using a liquid chromatograph mass spectrometer described in paragraphs
[0710] to
[0720] of International Publication No. 2018 / 181904. The apparatus used was an Agilent 1260 series HPLC / 6460S, and the column used was an Imtakt Cadenza CD-C18.
[0082] <Content of compound represented by formula (S2)> The content of the compound represented by the above formula (S2) relative to the total mass of particles in the aqueous dispersion obtained in each example described below was calculated by a method using an aqueous dispersion among the measurement methods using a liquid chromatograph mass spectrometer described in paragraphs
[0721] to
[0732] of International Publication No. 2018 / 181904. The apparatus used was an Agilent 1260 series HPLC / 6460S, and the column used was an Imtakt Cadenza CD-C18.
[0083] <Concentration of fluorine-based emulsifier in raw material liquid> The concentration of the fluorine-based emulsifier relative to the total mass of the fluorine-containing polymer in the raw material liquid was calculated from the charged amount.
[0084] <Crystallization energy> The melting point and crystallization energy were measured using a Perkin Elmer DSC8500. Specifically, 5 mg of a sample for measurement was weighed out and placed in an aluminum sample pan, and the sample was heated to 200°C at a heating rate of 10°C / min in an air atmosphere and held for 1 minute. The sample was then heated to 380°C at a heating rate of 10°C / min. The sample was held at 380°C for 1 minute and cooled to 200°C at a heating rate of 10°C / min. The peak top temperature resulting from thermal melting of the sample observed during heating from 200°C to 380°C was taken as the melting point, and the crystallization energy was calculated from the peak area observed during cooling from 380°C to 200°C. The smaller the absolute value of the crystallization energy, the higher the molecular weight.
[0085] <Temperature T> The temperature T was measured using a Perkin Elmer DSC8500 differential scanning calorimeter. Specifically, 10 mg of a sample for measurement was weighed out and placed in an aluminum sample pan, and the sample was heated from -20°C to 370°C at a heating rate of 10°C / min in an air atmosphere. The temperature at which the maximum heat absorption was observed in the range of 10 to 35°C was determined as temperature T.
[0086] [Production of raw material solution A] Ultrapure water (717 g), PMVE (50 g), and TFE (8 g) were charged into a 1.3 L stainless steel pressure reactor, and the temperature was raised to 90° C. while stirring at 500 rpm. Next, an aqueous solution of ammonium persulfate (3.6 mass%, 5 cc) was added to initiate polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 2 g of TFE was injected, the reactor was cooled to terminate the polymerization reaction. After the gas remaining in the reactor was collected, the liquid was extracted. This liquid was used as raw material liquid A. After the raw material liquid A was freeze-aggregated and filtered, the resulting fluoropolymer 1A was analyzed by NMR, and as a result, it was found that the TFE unit / PMVE unit ratio was 52 / 48 (molar ratio) and the Tg was -5.9°C.
[0087] [Production of raw material solution B] Dowex Monosphere 650C (manufactured by DuPont, cation exchange resin, 20 g) was added to the above raw material liquid A (490 g). 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration. Purolite A300 (manufactured by Purolite, anion exchange resin, 20 g) was added to the separated raw material liquid. 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration to obtain raw material liquid B. In raw material liquid B, particles of fluoropolymer 1A (average particle size: 87 nm) were dispersed in the aqueous medium, and the content of fluoropolymer 1A in raw material liquid B was 0.6 mass % based on the total mass of raw material liquid B.
[0088] [Production of raw material solution C] Ultrapure water (717 g), PMVE (55 g), TFE (9 g), and an aqueous ammonia solution (30% by mass, 1 drop) were charged into a 1.3 L stainless steel pressure reactor, and the temperature was raised to 90° C. while stirring at 500 rpm. Next, an aqueous ammonium persulfate solution (3.6% by mass, 5 cc) was added to start polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 2 g of TFE was injected, the reactor was cooled to terminate the polymerization reaction. After the gas remaining in the reactor was collected, the liquid was extracted. This liquid was used as raw material liquid C. After freeze-flocculation of the raw material liquid C, it was filtered off, and the resulting fluoropolymer 1C was analyzed by NMR, and as a result, it was found that the TFE unit / PMVE unit ratio was 52.4 / 47.6 (molar ratio) and the Tg was -5.3°C.
[0089] [Production of raw material solution D] Dowex Monosphere 650C (manufactured by DuPont, cation exchange resin, 20 g) was added to the above raw material liquid C (490 g). 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration. Purolite A300 (manufactured by Purolite, anion exchange resin, 20 g) was added to the separated raw material liquid. 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration to obtain raw material liquid D. In raw material liquid D, particles of fluoropolymer 1C (average particle size: 23 nm) were dispersed in the aqueous medium, and the content of fluoropolymer 1C in raw material liquid D was 0.7 mass % based on the total mass of raw material liquid D.
[0090] [Production of raw material solution E] Ultrapure water (717 g) and TFE (43 g) were charged into a 1.3 L stainless steel pressure reactor, and the temperature was raised to 90° C. while stirring at 500 rpm. Next, an aqueous solution of ammonium persulfate (3.6 mass%, 5 cc) was added to initiate polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 2 g of TFE was injected, the reactor was cooled to terminate the polymerization reaction. After the gas remaining in the reactor was collected, the liquid was extracted. This liquid was used as raw material liquid E. Raw material liquid E was freeze-aggregated and then filtered to obtain fluoropolymer 1E. The Tg of fluoropolymer 1E was 110°C.
[0091] [Production of raw material solution F] Dowex Monosphere 650C (manufactured by DuPont, cation exchange resin, 20 g) was added to the above raw material liquid E (490 g). 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration. Purolite A300 (manufactured by Purolite, anion exchange resin, 20 g) was added to the filtered raw material liquid. 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration to obtain raw material liquid F. In raw material liquid F, particles of fluoropolymer 1E (average particle size 80 nm) were dispersed in an aqueous medium, and the content of fluoropolymer 1E was 0.48 mass% based on the total mass of raw material liquid F.
[0092] [Production of raw material solution G] Ultrapure water (740g), sodium sulfite (88mg), n-BMA (n-butyl methacrylate, 330mg), iron(II) sulfate heptahydrate (11mg), and Chelate HC (17mg) were charged into a 1.2L stainless steel pressure reactor, and the temperature was raised to 60℃ while stirring at 500rpm. Next, an aqueous potassium persulfate solution (5.0% by mass, 3.8cc) was added, and polymerization was carried out for 60 minutes. After the polymerization reaction was completed, the liquid was withdrawn. This liquid was designated as raw material liquid G. After the raw material liquid G was heated to remove water, the residue was dried by heating to obtain a hydrocarbon polymer 1G (poly(n-BMA)). The Tg of the hydrocarbon polymer 1G was 20°C.
[0093] [Production of raw material solution H] Dowex Monosphere 650C (manufactured by DuPont, cation exchange resin, 20 g) was added to the above raw material liquid G (490 g). 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration. Purolite A300 (manufactured by Purolite, anion exchange resin, 20 g) was added to the filtered raw material liquid. 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration to obtain raw material liquid H. In raw material liquid H, particles of hydrocarbon polymer 1G (average particle size: 89 nm) were dispersed in an aqueous medium, and based on the amount of n-BMA charged, the content of hydrocarbon polymer 1G was 0.044 mass% relative to the total mass of raw material liquid H.
[0094] [Production of raw material solution I] Ultrapure water (717 g), PMVE (55 g), TFE (9 g), and an aqueous ammonia solution (30% by mass, 1 drop) were charged into a 1.3 L stainless steel pressure reactor, and the temperature was raised to 90 ° C. while stirring at 500 rpm. Next, an aqueous ammonium persulfate solution (3.6% by mass, 5 cc) was added to start polymerization. Since the pressure in the reactor decreased with the start of polymerization, TFE was added to keep the pressure constant. When 1 g of TFE was injected, the reactor was cooled to 20 ° C., and the polymerization reaction was terminated. After recovering the gas remaining in the reactor, nitrogen was injected up to 0.2 MPaG, and the temperature was raised to 90 ° C. The reactor was heated for 3 h, cooled, and the liquid was extracted. This liquid was used as raw material liquid I. Raw material liquid I was freeze-aggregated and then filtered. The resulting fluoropolymer 1I was analyzed by NMR, and as a result, it was found that the TFE unit / PMVE unit ratio was 52 / 48 (molar ratio) and the Tg was -5.5°C.
[0095] [Production of raw material solution J] Dowex Monosphere 650C (manufactured by DuPont, cation exchange resin, 20 g) was added to the above raw material liquid I (490 g). 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration. Purolite A300 (manufactured by Purolite, anion exchange resin, 20 g) was added to the filtered raw material liquid. 60 minutes after the start of stirring, the raw material liquid and the ion exchange resin were separated by filtration to obtain raw material J. In raw material liquid J, particles of fluoropolymer 1I (average particle size 28 nm) are dispersed in an aqueous medium, and the content of fluoropolymer 1I is 0.36 mass% based on the total mass of raw material liquid J.
[0096] [Production of raw material solution K] Ultrapure water (45.4 kg) and PMVE (1.1 kg) were charged into a 60.5 L stainless steel pressure reactor equipped with a baffle plate and a stirrer, and the temperature was raised to 90°C while stirring at 170 rpm. Next, TFE (72 g) and an aqueous solution of ammonium persulfate (7.7 mass%, 150 g) were added to initiate polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 165 g of TFE was injected, the reactor was cooled and the polymerization reaction was terminated. This liquid was used as raw material liquid K. Raw material liquid K contained fluoropolymer 1K. The raw material liquid K was freeze-aggregated and then filtered. The resulting fluoropolymer 1K was analyzed by NMR, and as a result, it was found that the TFE unit / PMVE unit ratio was 43 / 57 (molar ratio) and the Tg was -5°C.
[0097] [Production of raw material liquid L] Two ion exchange resin packed columns filled with Dowex Monosphere 650C (manufactured by DuPont, cation exchange resin, 843 mL) and Purolite A300 (manufactured by Purolite, anion exchange resin, 843 mL) were prepared, and raw material liquid K was passed through them to obtain raw material liquid L. In raw material liquid L, particles of fluoropolymer 1K (average particle size: 50 nm) are dispersed in an aqueous medium, and the content of fluoropolymer 1K relative to the total mass of raw material liquid L is 0.77 mass %.
[0098] [Example 1] Ultrapure water (121 g), raw material solution B (475 g), and WAX (28 g) were charged into a 1.0 L stainless steel pressure reactor to obtain aqueous dispersion B. Aqueous dispersion B was heated to 70°C while stirring at 260 rpm. TFE was injected until the pressure in the reactor reached 1.4 MPaG, and an aqueous solution of APS (ammonium persulfate) (0.2 mass%, 5 ml) was added to start polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 110 g of TFE was injected, the reactor was cooled and the polymerization reaction was terminated. The polymerization time was 220 minutes. The content of the fluoropolymer 1A in the aqueous dispersion B was 0.48% by mass. The content (solid content concentration) of the fluoropolymer 1A in the aqueous dispersion B was determined by heating 2.0 g of the aqueous dispersion B at 170° C. for 20 minutes, weighing the mass of the residue, and calculating the solid content concentration according to the following formula. The solid content concentration was calculated in the same manner for each of the examples described later, except that the type of the aqueous dispersion was changed to that used in each example. "Solid content concentration (mass%) = 100 × heating residue of aqueous dispersion B (g) / mass of aqueous dispersion B (2 g)" In addition, the concentration of the fluorine-containing emulsifier was 0 ppm by mass relative to the total mass of the fluorine-containing polymer 1A in the aqueous dispersion B. In addition, when the amount of the aqueous medium in the aqueous dispersion B used in the polymerization was taken as 100 parts by mass, the amount of the monomer (TFE) used in the polymerization was 18.5 parts by mass. After collecting the gas remaining in the reactor, the liquid was extracted. This liquid was designated as aqueous dispersion 1. Aqueous dispersion 1 was a dispersion in which particles (average particle size 228 nm) containing fluoropolymer 1A and fluoropolymer 2A were dispersed in an aqueous medium, and had a solid content concentration of 16.0% by mass. The particles in the obtained aqueous dispersion 1 were aggregated and filtered to obtain PTFE. The melting point of the PTFE dried at 150°C was 338°C and the crystallization energy was -35 J / g. The temperature T was 15°C. After drying, the composition was calculated using NMR, and the result was TFE unit / PMVE unit = 99.1 / 0.9 (molar ratio). In addition, in aqueous dispersion 1, the contents of the compound represented by formula (S1) and the compound represented by formula (S2) relative to the total mass of the particles in aqueous dispersion 1 were both 100 ppb by mass or less.
[0099] [Example 2] Ultrapure water (121 g), raw material liquid D (475 g), and WAX (28 g) were charged into a 1.0 L stainless steel pressure reactor to obtain aqueous dispersion D. Aqueous dispersion D was heated to 70°C while stirring at 260 rpm. TFE was injected until the pressure in the reactor reached 1.4 MPaG, and an aqueous APS solution (0.2 mass%, 5 ml) was added to start polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 170 g of TFE was injected, the reactor was cooled to terminate the polymerization reaction. The polymerization time was 282 minutes. The content of the fluoropolymer 1C in the aqueous dispersion D was 0.56% by mass based on the total mass of the aqueous dispersion D. In addition, the concentration of the fluorine-containing emulsifier was 0 ppm by mass relative to the total mass of the fluorine-containing polymer 1C in the aqueous dispersion D. In addition, when the amount of the aqueous medium used in the aqueous dispersion D used in the polymerization was taken as 100 parts by mass, the amount of the monomer (TFE) used in the polymerization was 28.5 parts by mass. After the gas remaining in the reactor was collected, the liquid was withdrawn. This liquid was designated as aqueous dispersion 2. Aqueous dispersion 2 was a dispersion in which particles (average particle diameter 258 nm) containing fluoropolymer 1C and fluoropolymer 2C were dispersed in an aqueous medium, and had a solid content concentration of 22.3% by mass. The particles in the obtained aqueous dispersion 2 were aggregated and filtered to obtain PTFE. The melting point of the PTFE dried at 150°C was 338°C and the crystallization energy was -33 J / g. The temperature T was 17°C. After drying, the composition was calculated using NMR, and the result was TFE unit / PMVE unit = 99.3 / 0.7 (molar ratio). In addition, in aqueous dispersion 2, the contents of the compound represented by formula (S1) and the compound represented by formula (S2) relative to the total mass of the particles in aqueous dispersion 2 were both 100 ppb by mass or less.
[0100] [Example 3] Ultrapure water (121 g), raw material liquid F (475 g), and WAX (28 g) were charged into a 1.0 L stainless steel pressure reactor to obtain aqueous dispersion F. Aqueous dispersion F was heated to 70°C while stirring at 260 rpm. TFE was injected until the pressure in the reactor reached 1.4 MPaG, and an aqueous APS solution (0.2 mass%, 5 ml) was added to start polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 70 g of TFE was injected, the reactor was cooled to terminate the polymerization reaction. The polymerization time was 185 minutes. After the gas remaining in the reactor was recovered, the liquid was extracted, but the entire amount had flocculated, and it was not possible to obtain an aqueous dispersion in which fluoropolymer particles were dispersed in an aqueous medium.
[0101] [Example 4] Raw material liquid H (596 g) and WAX (28 g) were charged into a 1.0 L stainless steel pressure reactor, and the temperature was raised to 70°C while stirring at 260 rpm. TFE was injected until the pressure in the reactor reached 1.4 MPaG, and an APS aqueous solution (0.2 mass%, 5 ml) was added to start polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 70 g of TFE was injected, the reactor was cooled and the polymerization reaction was terminated. The polymerization time was 470 minutes. After collecting the gas remaining in the reactor, the liquid was extracted. This liquid was designated as aqueous dispersion 4. Aqueous dispersion 4 was a dispersion in which particles (average particle diameter 278 nm) containing hydrocarbon polymer 1G and fluoropolymer 2G were dispersed in an aqueous medium, and had a solid content concentration of 10.2 mass%. Since the solid concentration of Aqueous Dispersion 4 is low, it can be said that the fluorine-containing polymer could not be produced efficiently. The particles in the obtained aqueous dispersion 4 were aggregated and filtered to obtain PTFE. The melting point of the PTFE dried at 150°C was 338°C and the crystallization energy was -27 J / g. The temperature T was 20°C. In addition, in aqueous dispersion 4, the contents of the compound represented by formula (S1) and the compound represented by formula (S2) relative to the total mass of the particles in aqueous dispersion 4 were both 100 ppb by mass or less.
[0102] [Example 5] Ultrapure water (121 g), raw material liquid J (475 g), and WAX (28 g) were charged into a 1.0 L stainless steel pressure reactor to obtain aqueous dispersion J. Aqueous dispersion J was heated to 70°C while stirring at 260 rpm. TFE was injected until the pressure in the reactor reached 1.4 MPaG, and an aqueous solution of DSAP (disuccinic acid peroxide) (0.45 mass%, 3 ml) was added to start polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 170 g of TFE was injected, the reactor was cooled and the polymerization reaction was terminated. The polymerization time was 426 minutes. The content of the fluoropolymer 1I was 0.29% by mass based on the total mass of the aqueous dispersion J. In addition, the concentration of the fluorine-containing emulsifier was 0 ppm by mass based on the total mass of the fluorine-containing polymer 1I in the aqueous dispersion J. In addition, when the amount of the aqueous medium used in the aqueous dispersion J used in the polymerization was taken as 100 parts by mass, the amount of the monomer (TFE) used in the polymerization was 28.5 parts by mass. After the gas remaining in the reactor was collected, the liquid was extracted. This liquid was designated as Aqueous Dispersion 5. Aqueous Dispersion 5 was a dispersion in which particles (average particle diameter 262 nm) containing fluoropolymer 1I and fluoropolymer 2I were dispersed in an aqueous medium, and had a solid content concentration of 21.3 mass%. The particles in the obtained aqueous dispersion 5 were aggregated and filtered to obtain PTFE. The melting point of the PTFE dried at 150°C was 345°C and the crystallization energy was -17.5 J / g. The temperature T was 17°C. After drying, the composition was calculated using NMR, and the result was TFE unit / PMVE unit = 99.6 / 0.4 (molar ratio). In addition, in aqueous dispersion 5, the contents of the compound represented by formula (S1) and the compound represented by formula (S2) were both 100 ppb by mass or less relative to the total mass of the particles in aqueous dispersion 5.
[0103] [Example 6] Ultrapure water (9.64 kg), raw material liquid L (42.0 kg), and WAX (1324 g) were charged into a 100 L stainless steel pressure reactor to obtain aqueous dispersion L. The aqueous dispersion L was heated to 70°C and stirring was started. TFE was injected until the pressure in the reactor reached 1.76 MPaG, and an aqueous DSAP solution (0.2 mass%, 1 L) was added to start polymerization. As the polymerization started, the pressure in the reactor decreased, so TFE was added to keep the pressure constant. When 14.0 kg of TFE was injected, the reactor was cooled and the polymerization reaction was terminated. The polymerization time was 154 minutes. The content of the fluoropolymer 1K relative to the total mass of the aqueous dispersion L was 0.62 mass %. In addition, the concentration of the fluorine-based emulsifier relative to the total mass of the fluorine-containing polymer 1K in the aqueous dispersion L was 0 ppm by mass. In addition, when the amount of the aqueous medium used in the aqueous dispersion L used in the polymerization was taken as 100 parts by mass, the amount of the monomer (TFE) used in the polymerization was 27.1 parts by mass. After the gas remaining in the reactor was collected, the liquid was extracted. This liquid was designated as Aqueous Dispersion 6. Aqueous Dispersion 6 was a dispersion in which particles (average particle diameter 200 nm) containing fluoropolymer 1K and fluoropolymer 2K were dispersed in an aqueous medium, and had a solid content concentration of 21 mass%. The particles in the obtained aqueous dispersion 6 were aggregated and filtered to obtain PTFE. The melting point of the PTFE dried at 150°C was 344°C and the crystallization energy was -16 J / g. The temperature T was 17°C. After drying, the composition was calculated using NMR, and the result was TFE unit / PMVE unit = 99.1 / 0.9 (molar ratio). In addition, in aqueous dispersion 7, the contents of the compound represented by formula (S1) and the compound represented by formula (S2) relative to the total mass of the particles in aqueous dispersion 2 were both 100 ppb by mass or less.
[0104] [Example 7] The raw material liquid B was freeze-aggregated and then filtered, and the resulting fluoropolymer 1B (0.2 g) was mixed with PTFE powder (manufactured by AGC, Fluon (registered trademark) PTFE CD145E, 9.8 g) to obtain a solid composition 7. The temperature T was 22.1°C.
[0105] [evaluation] <Colorability> 12 g of the dried particles obtained in each example was weighed out and pressed at a pressure of 0.78 MPaG for 2 minutes to form a cylindrical shape with a diameter of 26 mm and a height of 8 mm. The obtained molded body (pellet) was heated at 380°C in air for 30 minutes and cooled to room temperature (25°C). After that, the number of black foreign objects on the pellet surface was visually counted, and the colorability was evaluated according to the following criteria. The results are shown in Table 1. In the table, "-" indicates that the coloring property was not evaluated. A: 0 to 4 black foreign matters B: 5 or more black foreign bodies
[0106] [Table 1]
[0107] According to the process for producing a fluoropolymer of the present invention, it was shown that a fluoropolymer can be efficiently produced using an aqueous medium with a small environmental load and without requiring an emulsifier (Examples 1, 2, 5 and 6). Furthermore, comparison of Examples 1, 2 and 5 showed that if a heating step of heating the aqueous medium in which the first fluoropolymer is dispersed is performed after obtaining the first fluoropolymer, a high molecular weight PTFE can be obtained (Example 5). In contrast, in Examples 3 and 4, the fluoropolymer could not be produced efficiently.
[0108] The entire contents of the specification, claims, and abstract of Japanese Patent Application No. 2023-063511, filed on April 10, 2023, are hereby incorporated by reference as the disclosure of the present invention.
Claims
1. A method for producing a fluoropolymer, comprising polymerizing a monomer containing tetrafluoroethylene in an aqueous dispersion containing a first fluoropolymer having a glass transition temperature of 10° C. or lower and an aqueous medium to produce a second fluoropolymer different from the first fluoropolymer, comprising: before the start of polymerization of the monomers, the content of the first fluorinated polymer is 0.01 to 4.0% by mass based on the total mass of the aqueous dispersion, The method for producing a fluorine-containing polymer, wherein the concentration of the fluorine-containing emulsifier is 100 ppm by mass or less based on the total mass of the first fluorine-containing polymer in the aqueous dispersion before initiation of polymerization of the monomers.
2. The method for producing a fluorine-containing polymer according to claim 1, wherein the first fluorine-containing polymer contains units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether).
3. The method for producing a fluorine-containing polymer according to claim 2, wherein the first fluorine-containing polymer contains 20 to 60 mol% of units based on perfluoro(alkyl vinyl ether) relative to the total of the units based on tetrafluoroethylene and the units based on perfluoro(alkyl vinyl ether).
4. The process for producing a fluorine-containing polymer according to claim 1 or 2, wherein the amount of the monomer used is 1 to 50 parts by mass per 100 parts by mass of the aqueous medium used.
5. The process for producing a fluorine-containing polymer according to claim 1 or 2, wherein the monomers are polymerized in the presence of a polymerization initiator.
6. An aqueous dispersion comprising an aqueous medium, a first fluoropolymer having a glass transition temperature of 10°C or lower, and a second fluoropolymer which contains units based on tetrafluoroethylene and is different from the first fluoropolymer, wherein a temperature T showing a maximum endothermic amount in the range of 10 to 35°C of a solid composition obtained by aggregating the aqueous dispersion, as measured by the following method, is 19°C or lower; The content of the first fluorine-containing polymer is 0.1 to 5 mass % based on the total mass of the solid composition. How to measure temperature T: A solid composition that has not been heated to a temperature of 300° C. or higher is measured by a differential scanning calorimeter at a heating rate of 10° C. / min.
7. A solid composition comprising a first fluoropolymer having a glass transition temperature of 10°C or lower, and a second fluoropolymer which contains a unit based on tetrafluoroethylene and is different from the first fluoropolymer, wherein the temperature T showing the maximum endothermic amount of the solid composition in the range of 10 to 35°C, as measured by the following method, is 19°C or lower; A solid composition, wherein the content of the first fluorine-containing polymer is 0.1 to 5 mass% based on the total mass of the solid composition. How to measure temperature T: A solid composition that has not been heated to a temperature of 300° C. or higher is measured by a differential scanning calorimeter at a heating rate of 10° C. / min.
8. A solid composition obtained by agglomerating the aqueous dispersion according to claim 6, which has a maximum endothermic temperature T of 19°C or lower in the range of 10 to 35°C. How to measure temperature T: A solid composition that has not been heated to a temperature of 300° C. or higher is measured by a differential scanning calorimeter at a heating rate of 10° C. / min.
9. the content of units based on perfluoro(alkyl vinyl ether) is 0.1 to 5.0 mol % relative to the total of all units of the first fluorine-containing polymer and the second fluorine-containing polymer, The aqueous dispersion according to claim 6, wherein each of the content of the compound represented by formula (S1) and the content of the compound represented by formula (S2) is 100 ppb by mass or less relative to the total mass of the first fluorinated polymer and the second fluorinated polymer. Formula (S1): H-(CF 2 ) n―1 -COOM Formula (S2): H-(CF 2 ) n -SO 3 M In formula (S1) and formula (S2), M is independently a hydrogen atom, Na, K, or NH 4 and each n independently represents 8 or 10.
10. A solid composition comprising a first fluorine-containing polymer having a glass transition temperature of 10° C. or lower, and a second fluorine-containing polymer which contains a unit based on tetrafluoroethylene and is different from the first fluorine-containing polymer, the content of units based on perfluoro(alkyl vinyl ether) is 0.1 to 5.0 mol % relative to the total of all units of the first fluorine-containing polymer and the second fluorine-containing polymer, The solid composition according to claim 7, wherein each of the content of the compound represented by formula (S1) and the content of the compound represented by formula (S2) is 100 ppb by mass or less relative to the total mass of the first fluorinated polymer and the second fluorinated polymer. Formula (S1): H-(CF 2 ) n―1 -COOM Formula (S2): H-(CF 2 ) n -SO 3 M In formula (S1) and formula (S2), M is independently a hydrogen atom, Na, K, or NH 4 and each n independently represents 8 or 10.
Citation Information
Patent Citations
Aqueous fluorine-containing dispersion solution as well as preparation method and application thereof
CN107778412A
[shinkinahunmatsujiyouhuruoroerasutoma[shinkinahunmatsujiyouhuruoroerasutoma] -
JP1975084650A
Fluoropolymers produced by aqueous polymerization using dispersed microparticles of fluorinated ionomers.
JP2012513530A
Method for producing melt-moldable fluororesin
WO2007046377A1
Production method for polytetrafluoroethylene aqueous dispersion
WO2014084400A1